Analysis of the Performance Report of the Environment Agency of North Sumatra Utara - Riza Ayu Asmita; Nadya Maulidya Manurung; Annio Indah Lestari Nasution (Journal of Indonesian Management, 2022)
This journal reviews the performance report by the Environmental Agency of North Sumatra Province in 2021. This study aims to describe how the performance report is carried out by the Environmental Agency of North Sumatra Province. This type of research uses a qualitative approach, including library research. The source of this research is secondary data such as report data and related journals. Performance reporting is a form of accountability for each government agency for the implementation of programs and budgets. Performance report based on agreement, performance appraisal and performance evaluation. The results showed that the performance planning carried out was the 2019-2023 Strategic Plan (Renstra). In realizing the vision and mission of the Regional Head and to achieve the targets of the Main Performance Indicators (IKU), the North Sumatra Provincial Environment Service establishes a work program. The achievement of the performance indicators against the national target is very good because it is above the target set in the Strategic Plan of the Ministry of Environment and Forestry for the Year 2020-2024.